1998
DOI: 10.1038/sj.onc.1201996
|View full text |Cite
|
Sign up to set email alerts
|

Differential loss of heterozygosity at 7q31.2 in follicular and papillary thyroid tumors

Abstract: We analysed 42 di erentiated thyroid tumors including 15 follicular adenomas (FA), 13 papillary thyroid cancers (PTC) and 14 follicular thyroid carcinomas (FTC) with 13 microsatellite markers speci®c for the long arm of human chromosome 7 within 7q31; this region is deleted frequently in several other tumor types. Overall, 20 of the 42 samples analysed (48%) displayed LOH with one or more of the markers tested. LOH was detected most frequently (78%) in FTC, the most malignant of the thyroid tumors. A smallest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The crucial point is, therefore, that the literature reports no clear-cut differences between FTC and PTC. Such differences have been shown by Zhang et al (32), and they are attributable to two markers on 7q31.2, separated by 2 centiMorgans: D7S 480 and D7S 490. Indeed, LOH, at the first and second loci, was absent in 2/2 informative PTC and in 4/4 informative PTC, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The crucial point is, therefore, that the literature reports no clear-cut differences between FTC and PTC. Such differences have been shown by Zhang et al (32), and they are attributable to two markers on 7q31.2, separated by 2 centiMorgans: D7S 480 and D7S 490. Indeed, LOH, at the first and second loci, was absent in 2/2 informative PTC and in 4/4 informative PTC, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…As to the FTC vs. FA distinction, we have already stressed that the LOH pattern given by our four markers is totally different from that seen in FA. Instead, using the two markers proposed by Zhang et al (32), one FTC had the same pattern as one FA, and another FTC had the same pattern as a second FA; only three FTC had LOH for both markers. Together with Segev et al (31), we propose that LOH could be used also at the cytological level, with the advantage of planning the correct therapeutic strategy well ahead of operation.…”
Section: Discussionmentioning
confidence: 99%
“…All caps were handled with gloves to reduce contamination and kept separately from the others during all the following experimental procedures. After microdissection and DNA extraction, polymerase chain reaction (PCR) was carried out in the presence of specific primers flanking the sequence of two microsatellite markers (D7S-1779 and D7S-2468) located at the chromosomal region 7q32 -34 (cytogenetic localization 150 -152 cM) previously reported to be altered in thyroid cancer (Zhang et al, 1998;Roque et al, 2001).…”
Section: Laser Capture Microdissection and Loss Of Heterozygosity (Lomentioning
confidence: 99%
“…Deletions involving this region have been observed in virtually every major tumor type, with loss of heterozygosity (LOH) found in up to 80% of breast (Bieche et al, 1992;Zenklusen et al, 1994a), prostate (Zenklusen et al, 1994c;Latil et al, 1995;Takahashi et al, 1995), pancreatic (Achille et al, 1996), colon (Zenklusen et al, 1995a), ovarian (Zenklusen et al, 1995b), and thyroid cancers (Zhang et al, 1998), with lower frequencies in renal cancers (Shridhar et al, 1997) and squamous cell carcinomas of the head and neck (Zenklusen et al, 1995a). Functional studies using microcell-mediated transfer of chromosome 7 have shown that introduction of a normal copy of chromosome 7 can restore senescence to human fibroblasts (Ogata et al, 1993) and suppress tumorigenicity of a murine squamous cell carcinoma cell line and the human prostate carcinoma cell line, PC-3 (Zenklusen et al, 1994b;Zenklusen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%